A method for preparing carbonized cementitious material-based ECC concrete
Through the reaction of carbon dioxide mineralization curing technology with materials such as pseudowollastonite, high ductility, strain-hardening carbonized cementitious material-based ECC concrete is prepared, which solves the problem of large carbon emissions of traditional ECC concrete and achieves efficient carbon emission reduction and Improved mechanical properties.
Patent Information
- Application Number
- CN202411086755.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-08
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-08
AI Technical Summary
Traditional ECC concrete emits a large amount of carbon during production and application, resulting in an increase in environmental load, limiting its widespread use in infrastructure.
Carbon dioxide mineralization curing concrete technology is used to react carbon dioxide with materials such as pseudowollastonite, dicalcium silicate and wollastonite to form calcium carbonate and amorphous silicon oxide, thereby preparing high ductility, strain hardening and multi-slit concrete. Cracked carbonized cementitious material based ECC concrete.
It significantly reduces the carbon emissions of ECC concrete, improves the mechanical properties of concrete, and achieves the sustainable development of carbonized cementitious material-based ECC concrete.
Smart Images

Figure CN118878263B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of low-carbon concrete material preparation, and in particular to a method for preparing carbonized cementitious material-based ECC concrete. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Engineered cementitious composites (ECC) have good tensile-hardening and multi-seam steady-state cracking properties, good toughness, durability and fatigue resistance, and broad application prospects. Since the main characteristics of ECC concrete design are that the aggregate proportion is small and the particle size is small, and the amount of cement is large, the ECC hydration heat release is concentrated, the shrinkage is large, and structural cracks are easily generated. In addition, traditional ECC concrete has high carbon emissions and heavy environmental load, which hinders its widespread application in infrastructure. How to reduce carbon dioxide emissions during the production and application of ECC concrete and achieve green transformation is one of the hot issues studied by scientists.
[0004] At present, waste concrete is often used to modify ECC to reduce carbon emissions. The basic principle is to use waste concrete fine powder to replace part of the cement or to use recycled aggregate to replace fine aggregate to prepare recycled ECC with high strength and high ductility. However, recycled aggregate and waste concrete fine powder contain a large number of pores and microcracks, have stronger water absorption, and relatively low strength. Therefore, this method has great limitations. In addition, carbon dioxide mineralization curing concrete technology is widely regarded as an effective technical route to reduce the carbon footprint of cement. The technical principle is to add industrial carbon dioxide emissions to the preparation process of concrete. Carbon dioxide reacts with calcium and magnesium ions to form minerals, which play a role in hardening concrete and consuming carbon dioxide. However, this technology is affected by many factors (such as relative humidity, carbon dioxide concentration, curing time, curing temperature, etc.), resulting in low overall mineralization efficiency, which seriously restricts the development of carbon dioxide mineralization curing technology. Therefore, how to use carbon dioxide mineralization curing concrete to reduce the carbon footprint of ECC concrete is a difficult problem that needs to be solved in the development of ECC. Summary of the invention
[0005] In view of the above problems, the present invention provides a method for preparing carbonized cementitious material-based ECC concrete, which uses carbon dioxide mineralization and concrete curing technology to prepare high-ductility, strain-hardening, and multi-crack ECC concrete, providing a new way to reduce the carbon emissions of ECC concrete and achieve sustainable development. Specifically, the technical solution of the present invention is as follows.
[0006] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0007] (1) Pseudowollastonite, dicalcium silicate and calcite are dispersed in water, and then polycarboxylate water reducer is added and stirred. After completion, the reaction system is evaporated to dryness to obtain a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer for standby use.
[0008] (2) Dispersing the organic fiber in a non-aqueous solvent and then adding the carbon-fixing mineral under stirring conditions, and continuing to stir after completion. Then separating the fiber and carbonizing it in CO2 gas to obtain modified organic fiber for later use.
[0009] (3) Take the following raw materials: quartz sand, the carbon-fixing mineral, the modified organic fiber, and a thickener. Mix the above raw materials with mixing water and stir evenly to form an ECC concrete slurry. Then, perform carbonization curing on the concrete structure made of the slurry to obtain carbonized cementitious material-based ECC concrete.
[0010] Furthermore, in step (1), the mass ratio of the pseudowollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2), calcite (3CaO·2SiO2), and polycarboxylate water reducer is 1~2:2~4:2~4:0.03~0.05.
[0011] Furthermore, in step (1), the solid-to-liquid ratio of the pseudowollastonite, dicalcium silicate, wollastonite and water is 1g:1-2g.
[0012] Furthermore, in step (1), the stirring treatment time is 8 to 10 hours, so that the polycarboxylate water-reducing agent is evenly attached to the surface of the pseudowollastonite, dicalcium silicate and wollastonite particles.
[0013] Furthermore, in step (1), the temperature of the evaporation treatment is 40-50° C. Optionally, evaporation to constant weight is performed at this temperature to obtain the carbon-fixing mineral modified on the surface of the polycarboxylate water-reducing agent.
[0014] Furthermore, in step (2), the organic fiber includes at least one of polyvinyl alcohol (PVA) fiber, polyethylene fiber, polypropylene fiber, polyacrylonitrile fiber, etc. Optionally, the organic fiber has a diameter of 10-30 μm and a length of 12-20 mm.
[0015] Furthermore, in step (2), the mass ratio of the organic fiber, the non-aqueous solvent, and the carbon-fixing mineral is 1:2-3:1-2. Optionally, the non-aqueous solvent includes at least one of ethanol, isopropanol, and the like.
[0016] Furthermore, in step (2), the stirring is continued for 2 to 4 hours to allow the carbon-fixing mineral to be loaded onto the surface of the organic fiber.
[0017] Furthermore, in step (2), the CO2 gas pressure of the carbonization treatment is 0.2-0.5 MPa, the carbonization temperature is 40-60°C, and the carbonization time is 12-24 hours.
[0018] Furthermore, in step (3), the ratio of the quartz sand, the carbon-fixing mineral, the modified organic fiber, the thickener, and the mixing water is 0.7-1 parts by weight: 0.9-1 parts by weight: 0.18-0.22 parts by weight: 0.005-0.01 parts by weight: 0.4-0.6 parts by weight.
[0019] Furthermore, in step (3), the particle size of the quartz sand is 60-140 mesh.
[0020] Furthermore, in step (3), the thickener includes at least one of methyl cellulose, polyacrylamide, etc.
[0021] Furthermore, in step (3), the CO2 gas pressure of the carbonization curing is 0.2-0.5 MPa, the carbonization temperature is 40-60°C, and the carbonization time is 12-24 hours.
[0022] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0023] The present invention uses the carbon dioxide mineralization curing concrete technology to prepare ECC concrete with high ductility, high strain hardening and multi-seam steady-state cracking characteristics, which provides a new way to reduce the carbon emissions of ECC concrete and achieve sustainable development. To this end, the present invention first uses the characteristics of polycarboxylate water-reducing agent that releases hydrogen ions and carboxyl main chains after hydrolysis, and adds polycarboxylate water-reducing agent to the dispersion of pseudo wollastonite, dicalcium silicate and calcite, so that the surface of pseudo wollastonite, dicalcium silicate and calcite particles is dissociated and activated. On the one hand, the surface of the particles is loosened, providing conditions for the adsorption and connection of the polycarboxylate water-reducing agent, and the polycarboxylate water-reducing agent can be well adsorbed on the loose particle surface using its carboxyl main chain. On the other hand, the dissociation causes the particles to release calcium ions, which are captured by the carboxyl main chain of the polycarboxylate water-reducing agent to form a complex coated on the surface of the particles, thereby enriching and anchoring the calcium ions on the particle surface, significantly increasing the calcium ion concentration on the particle surface, and forming the above-mentioned polycarboxylate water-reducing agent surface modified carbon-fixing mineral.
[0024] Furthermore, the present invention also uses the above-mentioned carbon-fixing mineral to modify the surface of organic fibers, and then performs carbonization treatment on this basis. This is because: when the organic fibers loaded with such carbon-fixing minerals are carbonized, calcium ions provided by the carbon-fixing mineral particles can be used to grow in situ with carbon dioxide to form calcium carbonate and amorphous silicon oxide. The specific chemical reaction is as follows:
[0025] CaO·SiO2+CO2+H2O→CaCO3+SiO2+H2O
[0026] 3CaO·2SiO2+3CO2+H2O→3CaCO3+2SiO2+H2O
[0027] On the one hand, the roughness of the organic fiber surface is significantly increased, which not only eliminates the transition zone between the organic fiber and the carbon-fixing mineral, so that the two are firmly combined, but also increases the bonding between the fiber and the carbonized cementitious material-based ECC concrete matrix prepared by the present invention, thereby improving the mechanical strength of the concrete. On the other hand, the organic fiber with increased roughness can also help prevent the problem of uneven mixing with other raw materials.
[0028] When the above-mentioned carbon-fixing mineral and modified organic fiber are used to prepare ECC concrete, in the carbonization curing stage, carbon dioxide will preferentially react with calcium ions on the surface of the carbon-fixing mineral to form calcium carbonate and silicon oxide. When the surface of the carbon-fixing mineral reacts to a certain extent, due to the difference in calcium ion concentration gradient, the calcium ions inside the carbon-fixing mineral will continue to diffuse outward due to the internal and external concentration difference, thereby being captured by the carboxyl main chain of the polycarboxylate water-reducing agent and continuing the carbonization reaction. So on and so forth, the degree of carbonization reaction is greatly promoted, more carbonization products are generated, and the mechanical strength of concrete is enhanced. At the same time, coupled with the good bonding force between the modified fiber and the concrete matrix, the ECC concrete of the present invention not only has the characteristics of high ductility, high strain hardening and multi-seam steady-state cracking, that is, it has good mechanical properties, but also consumes a large amount of carbon dioxide, greatly reduces the emission of carbon dioxide, reduces the carbon footprint of ECC concrete, helps to promote the green transformation of the cement industry, and provides a new way for the sustainable development of the cement industry. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.
[0030] Figure 1 This is a scanning electron microscope (SEM) image of the carbonized cementitious material-based ECC concrete prepared in Example 1 below.
[0031] Figure 2This is a crack width test diagram of the carbonized cementitious material-based ECC concrete prepared in the following Example 1.
[0032] Figure 3 This is a crack width test diagram of the carbonized cementitious material-based ECC concrete prepared in the following Example 4.
[0033] Figure 4 This is a crack width test diagram of the carbonized cementitious material-based ECC concrete prepared in the following Example 5. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.
[0035] Example 1
[0036] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0037] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 1.5 parts by weight: 3 parts by weight: 3 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 2 g. Then, polycarboxylate water reducer is added dropwise and stirred continuously for 10 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.04 parts by weight: 1.5 parts by weight. After completion, the obtained solid-liquid system is heated to 50°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0038] (2) PVA fibers (20 μm in diameter and 17 mm in length) were dispersed in 95% ethanol, and then the carbon-fixing mineral was added under stirring. The ratio of the fibers, ethanol, and carbon-fixing mineral was 1 g: 2 g: 1.5 g. After completion, stirring was continued for 3.5 hours. The fibers were then separated by filtration and spread in a glass dish filled with water with a thickness of 5 mm. The glass dish was then placed in a carbonization reactor, and CO2 gas was introduced. The gas pressure was set to 0.25 MPa, the temperature was 50 °C, and the reaction time was 24 h. After completing the above carbonization treatment, the modified organic fiber was obtained and set aside.
[0039] (3) Take the following proportions of raw materials: 0.8 parts by weight of quartz sand with a particle size distribution between 60 and 100 meshes, 1 part by weight of the carbon-fixing mineral prepared in this embodiment, 0.2 parts by weight of the modified organic fiber prepared in this embodiment, 0.01 parts by weight of hydroxymethyl cellulose, and 0.55 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.25MPa, the temperature to 50°C, and the reaction time to 24 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0040] The internal microstructure of the carbonized cementitious material-based ECC concrete prepared in this embodiment is as follows: Figure 1 As shown in the figure, it can be seen that the ECC concrete is fully hydrated, tiny hydration products (calcium carbonate) are formed on the surface of the particles, and gel-like silica gel connects the particles. The carbonization reaction of the carbon-fixing minerals is complete, and they are cross-linked to form a three-dimensional mesh gel structure system, thus ensuring good macroscopic mechanical properties.
[0041] 1. According to the Technical Specification for Strain Hardening Cement-based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width (such as Figure 2 The larger the value of the ultimate tensile strain, the better the performance. The smaller the value of the crack width, the better the performance.
[0042] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0043] .
[0044] Example 2
[0045] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0046] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 1 part by weight: 4 parts by weight: 2 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 1.5 g. Then, polycarboxylate water reducer is added dropwise and stirred for 8 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.03 parts by weight: 1 part by weight. After completion, the obtained solid-liquid system is heated to 40°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0047] (2) Disperse polyethylene fibers (diameter 10 μm, length 12 mm) in 90% ethanol, and then add the carbon-fixing mineral under stirring conditions, the ratio of the fibers, ethanol, and carbon-fixing mineral is 1 g: 3 g: 2 g. Continue stirring for 3.5 hours after completion. Then filter and separate the fibers, spread them in a glass dish filled with water, and the laying thickness is 3 mm. Then place the glass dish in a carbonization reactor, pass CO2 gas, set the air pressure to 0.5 MPa, the temperature to 40 ° C, and the reaction time to 18 h. After completing the above carbonization treatment, the modified organic fiber is obtained and set aside.
[0048] (3) Take the following proportions of raw materials: 1 part by weight of quartz sand with a particle size distribution between 80 and 140 meshes, 1 part by weight of the carbon-fixing mineral prepared in this embodiment, 0.22 parts by weight of the modified organic fiber prepared in this embodiment, 0.007 parts by weight of hydroxypropyl methylcellulose, and 0.6 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.5MPa, the temperature to 40°C, and the reaction time to 18 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0049] 1. According to the Technical Specification for Strain Hardening Cement-Based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width of the carbonized cementitious material-based ECC concrete prepared in this embodiment were tested.
[0050] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0051] .
[0052] Example 3
[0053] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0054] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 2 parts by weight: 2 parts by weight: 4 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 1 g. Then, polycarboxylate water reducer is added dropwise and stirred continuously for 9 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.05 parts by weight: 2 parts by weight. After completion, the obtained solid-liquid system is heated to 40°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0055] (2) Disperse polypropylene fibers (30 μm in diameter and 20 mm in length) in isopropanol, and then add the carbon-fixing mineral under stirring conditions. The ratio of the fibers, isopropanol, and carbon-fixing mineral is 1 g: 2.5 g: 1 g. Continue stirring for 4 hours after completion. Then filter and separate the fibers, and spread them in a glass dish filled with water with a thickness of 5 mm. Then place the glass dish in a carbonization reactor, introduce CO2 gas, set the pressure to 0.2 MPa, the temperature to 60 ° C, and the reaction time to 12 h. After completing the above carbonization treatment, the modified organic fiber is obtained and set aside.
[0056] (3) Take the following proportions of raw materials: 0.7 parts by weight of quartz sand with a particle size distribution between 80 and 100 meshes, 0.9 parts by weight of the carbon-fixing mineral prepared in this embodiment, 0.18 parts by weight of the modified organic fiber prepared in this embodiment, 0.005 parts by weight of polyacrylamide, and 0.4 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.2MPa, the temperature to 60°C, and the reaction time to 12h. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0057] 1. According to the Technical Specification for Strain Hardening Cement-Based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width of the carbonized cementitious material-based ECC concrete prepared in this embodiment were tested.
[0058] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0059] .
[0060] Example 4
[0061] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0062] (1) Pseudowollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 1.5 parts by weight: 3 parts by weight: 3 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 2 g. The obtained solid-liquid system is then heated to 50°C and kept warm to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of a polycarboxylate water-reducing agent is obtained and set aside.
[0063] (2) PVA fibers (20 μm in diameter and 17 mm in length) were dispersed in 95% ethanol, and then the carbon-fixing mineral was added under stirring. The ratio of the fibers, ethanol, and carbon-fixing mineral was 1 g: 2 g: 1.5 g. After completion, stirring was continued for 3.5 hours. The fibers were then separated by filtration and spread in a glass dish filled with water with a thickness of 5 mm. The glass dish was then placed in a carbonization reactor, and CO2 gas was introduced. The gas pressure was set to 0.25 MPa, the temperature was 50 °C, and the reaction time was 24 h. After completing the above carbonization treatment, the modified organic fiber was obtained and set aside.
[0064] (3) Take the following proportions of raw materials: 0.8 parts by weight of quartz sand with a particle size distribution between 60 and 100 meshes, 1 part by weight of the carbon-fixing mineral prepared in this embodiment, 0.2 parts by weight of the modified organic fiber prepared in this embodiment, 0.01 parts by weight of hydroxymethyl cellulose, and 0.55 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.25MPa, the temperature to 50°C, and the reaction time to 24 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0065] 1. According to the Technical Specification for Strain Hardening Cement-based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width (such as Figure 3 as shown) for testing.
[0066] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0067] .
[0068] Example 5
[0069] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0070] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 2 parts by weight: 2 parts by weight: 4 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 1 g. Then, polycarboxylate water reducer is added dropwise and stirred continuously for 9 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.05 parts by weight: 2 parts by weight. After completion, the obtained solid-liquid system is heated to 40°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0071] (2) Take the following proportions of raw materials: 0.7 parts by weight of quartz sand with a particle size distribution between 80 and 100 meshes, 0.9 parts by weight of the carbon-fixing mineral prepared in this embodiment, 0.18 parts by weight of polypropylene fiber (diameter 30 μm, length 20 mm), 0.005 parts by weight of polyacrylamide, and 0.4 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.2 MPa, the temperature to 60°C, and the reaction time to 12 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0072] 1. According to the Technical Specification for Strain Hardening Cement-based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width (such as Figure 4 as shown) for testing.
[0073] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0074] .
[0075] Example 6
[0076] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0077] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 1.5 parts by weight: 3 parts by weight: 3 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 2 g. Then, polycarboxylate water reducer is added dropwise and stirred continuously for 10 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.04 parts by weight: 1.5 parts by weight. After completion, the obtained solid-liquid system is heated to 50°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0078] (2) PVA fibers (20 μm in diameter and 17 mm in length) were dispersed in 95% ethanol, and then the carbon-fixing mineral was added under stirring. The ratio of the fibers, ethanol, and carbon-fixing mineral was 1 g: 2 g: 1.5 g. After completion, stirring was continued for 3.5 hours. The fibers were then separated by filtration and dried to obtain modified organic fibers for later use.
[0079] (3) Take the following proportions of raw materials: 0.8 parts by weight of quartz sand with a particle size distribution between 60 and 100 meshes, 1 part by weight of the carbon-fixing mineral prepared in this embodiment, 0.2 parts by weight of the modified organic fiber prepared in this embodiment, 0.01 parts by weight of hydroxymethyl cellulose, and 0.55 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.25MPa, the temperature to 50°C, and the reaction time to 24 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0080] 1. According to the Technical Specification for Strain Hardening Cement-Based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width of the carbonized cementitious material-based ECC concrete prepared in this embodiment were tested.
[0081] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0082] .
[0083] Example 7
[0084] A method for preparing carbonized cementitious material-based ECC concrete comprises the following steps:
[0085] (1) Pseudo-wollastonite (CaO·SiO2), dicalcium silicate (2CaO·SiO2) and calcite (3CaO·2SiO2) are added to water in a ratio of 1 part by weight: 4 parts by weight: 2 parts by weight and subjected to ultrasonic treatment to obtain a dispersion having a solid-liquid ratio of 1 g: 1.5 g. Then, polycarboxylate water reducer is added dropwise and stirred for 8 hours. The ratio of the polycarboxylate water reducer to pseudo-wollastonite is 0.03 parts by weight: 1 part by weight. After completion, the obtained solid-liquid system is heated to 40°C to allow the water therein to evaporate slowly. After constant weight, a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer is obtained for later use.
[0086] (2) Spread polyethylene fibers (10 μm in diameter and 12 mm in length) into a glass dish saturated with water to a thickness of 3 mm. Then place the glass dish in a carbonization reactor, introduce CO2 gas, set the pressure to 0.5 MPa, the temperature to 40°C, and the reaction time to 18 h. After the above carbonization treatment, the modified organic fibers are obtained and set aside.
[0087] (3) Take the following proportions of raw materials: 1 part by weight of quartz sand with a particle size distribution between 80 and 140 meshes, 1 part by weight of the carbon-fixing mineral prepared in this embodiment, 0.22 parts by weight of the modified organic fiber prepared in this embodiment, 0.007 parts by weight of hydroxypropyl methylcellulose, and 0.6 parts by weight of mixing water. Mix the above raw materials and stir evenly to form an ECC concrete slurry. Then pour the slurry into a mold, and demold it after hardening for 24 hours to form a concrete specimen. Then place the specimen in a carbonization reactor, introduce CO2 gas, set the air pressure to 0.5MPa, the temperature to 40°C, and the reaction time to 18 hours. After completing the above carbonization curing, a carbonized cementitious material-based ECC concrete is obtained.
[0088] 1. According to the Technical Specification for Strain Hardening Cement-Based Composite Materials Structures (T / CECS 1212-2022), the ultimate tensile strain and the corresponding crack width of the carbonized cementitious material-based ECC concrete prepared in this embodiment were tested.
[0089] 2. The compressive strength of the carbonized cementitious material-based ECC concrete prepared in this embodiment was tested according to the "Concrete Physical and Mechanical Properties Test Method Standard" (GBT 50081-2019). The test results of the above performance indicators are shown in the following table:
[0090] .
[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.
Claims
1. A method for preparing carbonized cementitious material-based ECC concrete, characterized in that: The steps include: (1) dispersing pseudowollastonite, dicalcium silicate and wollastonite in water, and then adding a polycarboxylate water reducer and stirring; after completion, the reaction system is evaporated to dryness to obtain a carbon-fixing mineral modified on the surface of the polycarboxylate water reducer for standby use; (2) dispersing the organic fiber in a non-aqueous solvent, and then adding the carbon-fixing mineral under stirring conditions, and continuing to stir after completion; then separating the fiber and carbonizing it in CO2 gas to obtain modified organic fiber for later use; (3) The following raw materials are taken: quartz sand, the carbon-fixing mineral, the modified organic fiber, and a thickener; the raw materials are mixed with mixing water and stirred evenly to form an ECC concrete slurry; then the concrete structure made of the slurry is carbonized and cured to obtain carbonized cementitious material-based ECC concrete.
2. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (1), the mass ratio of the pseudowollastonite, dicalcium silicate, wollastonite and polycarboxylate water reducer is 1-2:2-4:2-4:0.03-0.
05.
3. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (1), the solid-to-liquid ratio of the pseudowollastonite, dicalcium silicate, wollastonite and water is 1g:1-2g.
4. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (1), the stirring treatment time is 8 to 10 hours.
5. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (1), the temperature of the evaporation to dryness is 40-50°C.
6. The method for preparing carbonized cementitious material-based ECC concrete according to claim 5, characterized in that: The carbon-fixing mineral modified on the surface of the polycarboxylate water-reducing agent is obtained by evaporating to constant weight at the temperature.
7. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the organic fiber includes at least one of polyvinyl alcohol fiber, polyethylene fiber, polypropylene fiber, and polyacrylonitrile fiber.
8. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the diameter of the organic fiber is 10-30 μm and the length is 12-20 mm.
9. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the mass ratio of the organic fiber, the non-aqueous solvent, and the carbon-fixing mineral is 1:2-3:1-2.
10. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the non-aqueous solvent includes at least one of ethanol and isopropanol.
11. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the stirring time is 2 to 4 hours.
12. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (2), the CO2 gas pressure of the carbonization treatment is 0.2-0.5 MPa, the carbonization temperature is 40-60°C, and the carbonization time is 12-24 hours.
13. The method for preparing carbonized cementitious material-based ECC concrete according to claim 1, characterized in that: In step (3), the ratio of the quartz sand, the carbon-fixing mineral, the modified organic fiber, the thickener, and the mixing water is 0.7-1 parts by weight: 0.9-1 parts by weight: 0.18-0.22 parts by weight: 0.005-0.01 parts by weight: 0.4-0.6 parts by weight.
14. The method for preparing carbonized cementitious material-based ECC concrete according to any one of claims 1 to 13, characterized in that: In step (3), the CO2 gas pressure of the carbonization curing is 0.2-0.5 MPa, the carbonization temperature is 40-60°C, and the carbonization time is 12-24 hours.
15. The method for preparing carbonized cementitious material-based ECC concrete according to any one of claims 1 to 13, characterized in that: In step (3), the particle size of the quartz sand is 60-140 mesh.
16. The method for preparing carbonized cementitious material-based ECC concrete according to any one of claims 1 to 13, characterized in that: In step (3), the thickener includes at least one of methyl cellulose and polyacrylamide.
Citation Information
Patent Citations
Nanocrystalline nucleus suspension liquid based on industrial solid waste and preparation method thereof
CN111302350A
Sprayable PVA-ECC high-ductility cement-based composite material and preparation method thereof
CN112745085A